Chrysotoxum elegans LOEW 1841 - Samin, Najmeh; Sakenin, Hamid (Zenodo, 2015)
Chrysotoxum elegans LOEW, 1841 Material examined : West Azarbaijan province, Mahabad, 36°46'N 45°44'E, 1 ♀, 1 ♂, 22-29 June 2012. Distribution outside Iran : Fennoscandia south to Iberia and the Mediterranean; through central and southern Europe into European parts of Russia as far as the Caucasus Mountains and into Turkey. : Published as part of Samin, Najmeh & Sakenin, Hamid, 2015, A faunistic study on the hoverflies (Diptera: Syrphidae) from West Azarbaijan province, Iran, pp. 393-401 in Beiträge Zur Entomologie = Contributions to Entomology 65 (2) on page 396, DOI: 10.21248/contrib.entomol.65.2.393-401, http://zenodo.org/record/5371302